A Study Of The Relationship Between The Big Five Personality Dimensions And Job Involvement In A Foreign Based Bank/Financial Institution Institution In Penang - Eswaran, Sivaram (2008)
The relationship between the Big Five Personality Dimensions and job involvement was examined in a questionnaire study with a sample of one hundred and five (105) sales/customer service staff of a foreign based banking/financial institution in the Northern Region of Malaysia. Hypotheses were tested by means of hierarchical regression with the inclusion of a few moderating factors.